Three-dimensional network of hexagonal boron nitride filled with polydimethylsiloxane with high thermal conductivity and good insulating properties for thermal management applications. (2nd December 2022) - Liu, Li; Li, Ying; Yu, Xianglei; Du, Jinghong; Zhang, Jiamin; Li, Junpeng; Gan, Guoyou
Abstract: Electronic components tend to fail due to heat accumulation during use. As a result, thermally conductive and insulating polymer-matrix composites (PMCs) are in great demand in the electronics packaging industry. This study proposes a new hard-template approach for the construction of a three-dimensional hexagonal boron nitride foam (3D-BN) using PMMA microspheres as sacrificial materials. The 3D-BN is then filled with polydimethylsiloxane (PDMS) to create 3D-BN/PDMS composites with high thermally conductivities and good insulating properties. The results of various characterization analyses and 3D finite element simulation show that the 3D-BN is the fundamental factor in improving the thermal conductivity (TC) of the composites. Compared with nanoscale h-BN (nBN), micron h-BN (mBN) is more organized along the pore walls in 3D-BN, better utilizing the in-plane TC of h-BN while reducing the interface thermal resistance (ITR). The obtained lightweight composite exhibits a high TC of 1.868 Wm −1 K −1 and an ultrahigh volume electrical resistivity of 3.66 × 10 13  Ω m at 18.33 vol% mBN loading. This research provides a promising strategy for designing and fabricating thermal management PMCs. Graphical abstract: Image 1 Highlights: We propose a new hard-template approach for constructing 3D-BN using PMMA microspheres as sacrificial materials. Experimental tests and simulations address the impacts of 3D-BN on improving the thermal conductivity of PMCs. Micron h-BN (mBN) exhibits better heat transfer efficiency than nanoscale h-BN (nBN) in 3D-BN/PDMS.